Politics and the police in Scotland: the impact of devolution - Scott, Kenneth B. (Crime, law and social change, 2011)
The creation of a Scottish Parliament and Scottish government in 1999, under the process of devolution within the UK, created a significantly different constitutional and political landscape from that which preceded it. The impact on domestic issues in Scotland, such as policing, has been considerable. This is partly because of new structural arrangements, including the creation of a Justice Minister and a Justice Committee of the Parliament, and partly because of the significance of the law and order agenda within Scottish politics. This paper discusses the impact of these developments on the Scottish police. Analysis focuses on the growing involvement of the Scottish Parliament and Scottish governments in key areas such as constabulary independence, police accountability and the management of police resources. Through this discussion, the paper seeks to make a contribution to the debate about the relationship between the police and politics, and the extent to which policing in Scotland is becoming increasingly politicised.